2020
DOI: 10.3390/catal10050548
|View full text |Cite
|
Sign up to set email alerts
|

Simulation and Optimization of the CWPO Process by Combination of Aspen Plus and 6-Factor Doehlert Matrix: Towards Autothermal Operation

Abstract: This work aims to present an industrial perspective on Catalytic Wet Peroxide Oxidation (CWPO) technology. Herein, process simulation and experimental design have been coupled to study the optimal process conditions to ensure high-performance oxidation, minimum H2O2 consumption and maximum energetic efficiency in an industrial scale CWPO unit. The CWPO of phenol in the presence of carbon black catalysts was studied as a model process in the Aspen Plus® v11 simulator. The kinetic model implemented, based on 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Although mineralization was not itself as high as when using PC, as mentio fore, efficient use of H2O2 may impact the cost of the CWPO unit [44]. The main di observed with ηH 2 O 2 when using PC or HC catalyst may be ascribed to the slower position of H2O2 when applying HC (as shown in Figure 6).…”
Section: Coagulation-flocculation and Cwpomentioning
confidence: 95%
See 2 more Smart Citations
“…Although mineralization was not itself as high as when using PC, as mentio fore, efficient use of H2O2 may impact the cost of the CWPO unit [44]. The main di observed with ηH 2 O 2 when using PC or HC catalyst may be ascribed to the slower position of H2O2 when applying HC (as shown in Figure 6).…”
Section: Coagulation-flocculation and Cwpomentioning
confidence: 95%
“…It can be concluded that the objective was achieved, as in the CWPO reactions conducted with either PC or HC, an improvement in η H 2 O 2 was observed, which means that fewer parallel reactions other than organic matter oxidation took place. Since in a CWPO unit, H 2 O 2 is the main operational cost [44], conditions that result in a more efficient decomposition of the oxidant source are considered a key step in developing suitable CWPO processes [44].…”
Section: Ion Exchange Resin and Cwpomentioning
confidence: 99%
See 1 more Smart Citation
“…Among AOPs, catalytic wet peroxide oxidation (CWPO) can be highlighted due to its low cost and mild operation [10]. CWPO relies on the formation of highly oxidizing hydroxyl radicals from hydrogen peroxide through the action of a suitable catalyst [11]. CWPO has been tested for the oxidation of several organic compounds with distinct catalysts [12][13][14][15][16], showing effective results in the degradation of organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the running cost of a CWPO unit is mainly due to H2O2 consumption (Diaz de Tuesta et al, 2020), an efficient H2O2 consumption represents a fundamental parameter to be assessed to avoid the formation of molecular oxygen (Ribeiro et al, 2013). In this context, the efficiency of hydrogen peroxide consumption, determined as specified in Eq (1), was good for both catalysts, with advantage for Mon11F, probably because the catalyst favours the efficient use of radicals HO • , HOO • and O2 •to oxidize the organic matter, instead of leading to undesirable side reactions, enabling more efficient utilization of the oxidant.…”
Section: Resultsmentioning
confidence: 99%